Evolution of the ribbon-like organization of the Golgi apparatus in animal cells - Benvenuto, Giovanna; Leone, Serena; Astoricchio, Emanuele; Bormke, Sophia; Jasek, Sanja; D'Aniello, Enrico; Kittelmann, Maike; McDonald, Kent; Hartenstein, Volker; Baena, Valentina; Escrivà, Héctor; Bertrand, Stephanie; et al. (Cell reports, 2024)
The "ribbon," a structural arrangement in which Golgi stacks connect to each other, is considered to be restricted to vertebrate cells. Although ribbon disruption is linked to various human pathologies, its functional role in cellular processes remains unclear. In this study, we investigate the evolutionary origin of the Golgi ribbon. We observe a ribbon-like architecture in the cells of several metazoan taxa suggesting its early emergence in animal evolution predating the appearance of vertebrates. Supported by AlphaFold2 modeling, we propose that the evolution of Golgi reassembly and stacking protein (GRASP) binding by golgin tethers may have driven the joining of Golgi stacks resulting in the ribbon-like configuration. Additionally, we find that Golgi ribbon assembly is a shared developmental feature of deuterostomes, implying a role in embryogenesis. Overall, our study points to the functional significance of the Golgi ribbon beyond vertebrates and underscores the need for further investigations to unravel its elusive biological roles.